Pengaruh Tingkat Pendapatan, Literasi Digital, dan Lingkungan Sosial Terhadap Intensi Berinvestasi pada Generasi Z di DKI Jakarta - Iryuanita, Elvina; Saparuddin, Saparuddin; Zahra, Siti Fatimah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Investment trends in Indonesia have shown a significant increase, partly driven by the dominance of Generation Z as capital market investors. An interesting phenomenon emerges when Generation Z, despite having relatively low and unstable income, continues to dominate investment activities in the capital market. Based on this condition, this study aims to analyze the influence of Income Level, Digital Literacy, and Social Environment on Investment Intention among Generation Z in DKI Jakarta. This research uses primary data with a quantitative approach. The sample consists of 100 Generation Z respondents aged 20–27 years who already have income and reside in DKI Jakarta. The sampling technique was carried out using purposive sampling, with a questionnaire as the data collection instrument. The data were analyzed using multiple linear regression with the help of SPSS version 25. The partial test (t-test) results show that Income Level has no significant effect on Investment Intention, while Digital Literacy and Social Environment have a positive and significant effect. The simultaneous test (F-test) results indicate that Income Level, Digital Literacy, and Social Environment together have a significant positive effect on Investment Intention. These findings are expected to provide valuable insights for developing financial education strategies and investor protection programs targeting young investors in Indonesia.